Estimation of soil moisture levels at field capacity and wilting point by predictive models on a regional scale - P. Pérez Cutillas; G. González Barberá; Carmelo Conesa García (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.